2011
DOI: 10.1037/a0022012
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between activating affects, inhibitory affects, and self-compassion in patients with Cluster C personality disorders.

Abstract: In the short-term dynamic psychotherapy model termed "Affect Phobia Treatment," it is assumed that increase in patients' defense recognition, decrease in inhibitory affects (e.g., anxiety, shame, guilt), and increase in the experience of activating affects (e.g., sadness, anger, closeness) are related to enhanced self-compassion across therapeutic approaches. The present study aimed to test this assumption on the basis of data from a randomized controlled trial, which compared a 40-session short-term dynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 53 publications
(47 reference statements)
8
68
0
Order By: Relevance
“…Previous research using the ATOS found that increased levels of affect experiencing was related to a more compassionate and realistic sense of self and others (Berggraf, Ulvenes, Øktedalen, et al, 2014;Schanche, Stiles, McCullough, Svartberg, & Nielsen, 2011). In line with these findings and those of Fisher and colleagues (2016), we aimed to examine evidence of within-client associations between affect experiencing and changes in self-reported distress ratings on a session-by-session basis.…”
Section: Current Study and Research Objectivementioning
confidence: 55%
“…Previous research using the ATOS found that increased levels of affect experiencing was related to a more compassionate and realistic sense of self and others (Berggraf, Ulvenes, Øktedalen, et al, 2014;Schanche, Stiles, McCullough, Svartberg, & Nielsen, 2011). In line with these findings and those of Fisher and colleagues (2016), we aimed to examine evidence of within-client associations between affect experiencing and changes in self-reported distress ratings on a session-by-session basis.…”
Section: Current Study and Research Objectivementioning
confidence: 55%
“…This study relied on the Achievement of Therapeutic Objectives Scale (ATOS) developed by McCullough et al [60] which allows researchers to examine different therapeutic processes and the extent to which a patient is able to assimilate within the course of a session. Further process studies on larger samples using scales such as the ATOS are needed [65] to determine how defensive functioning modulates the patient's abilities to adaptively process and experience affect.…”
Section: Consider the Affect Associated With The Defense When Approprmentioning
confidence: 99%
“…Wolberg [10] indicates that current sources of stress (outside the therapy), and their interaction with personality needs and defenses be addressed before therapy can unfold in a productive fashion. These authors imply that what unfolds outside of therapy is of value and understanding the defensive processes that patients recount from their "outside" lives could be an equally valuable pursuit in-session [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. This is in line with Vaillant's work [18] that suggests that events from outside the therapeutic hour should not only be acknowledged but also dealt with before systematic intervention focusing on defenses in-session is undertaken.…”
Section: Attend To Defenses Used Both Inside and Outside Of The Theramentioning
confidence: 99%
“…Research inquiry into treating personality disorders with self-compassion has also ensued. Schanche, Stiles, McCullough, Svartberg, and Nielsen (2011) reported the development of self-compassion in individuals diagnosed with Cluster C personality disorders significantly predicted reductions of psychiatric symptoms, personality pathology, and relational challenges after therapy. Although the specific use of self-compassion in clinical applications is still being explored, results are promising thus far.…”
Section: Self-compassion and The Treatment Of Psychopathologymentioning
confidence: 99%